Positive Politeness Strategies in Jimmy Fallon interview with Angelina Jolie: Pragmatic Approach - Zipar Luhut Orlando Sirait; Zia Hisni Mubarak (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This research explores the application of positive politeness tactics during the conversation between Jimmy Fallon and Angelina Jolie on The Tonight Show Starring Jimmy Fallon. This study aims to classify the types of positive politeness strategies employed by each speaker and to demonstrate how both speakers used different forms of positive politeness in their dialogue. This study employed a qualitative methodology, gathering data from a publicly accessible YouTube video and examining the conversational data through the lens of Brown and Levinson's (1987) positive politeness theory related to language and the application of Language Forms or Argument Forms. As part of the analysis process, a detailed examination of the conversational exchanges between the two parties was conducted to identify and characterize instances of positive politeness, using language constructs such as words and phrases that reflect positive politeness. Out of the total 24 instances of data collected, 12 were identified as being specific positive politeness strategies used by one or the other conversational partner. The most frequently employed positive politeness strategy identified in the analysis was 'exaggeration,' which was identified five times. This discovery relates to the purpose of exaggeration as a means of demonstrating appreciation, approval and empathy for another person. From the information above, it is evident that positive politeness plays a crucial role when celebrities are interviewed in a casual and friendly way; moreover, there is scope for different approaches to leverage positive politeness as a means to foster an engaging and supportive atmosphere in interactions with others.